Consensus Statements on the Assessment of Older Drivers - Hogan, David B.; Scialfa, Charles T.; Caird, Jeff K. (Canadian Geriatrics Journal, 2014)
Background The rapidly increasing number of older drivers is accentuating the challenges in concurrently identifying older drivers posing an unacceptable risk if they continue to drive, while not discriminating against those capable of safely driving. Attendees of an invitational meeting about the assessment of older drivers were asked to participate in a modified Delphi process designed to develop consensus statements on the assessment of older drivers. Methods Forty-one non-student symposium attendees were invited to participate in two rounds of a survey, in which they were asked to indicate their level of agreement (or disagreement) on a five-point Likert scale to a series of statements about the assessment of older drivers. Consensus was defined as 80% + of respondents either agreeing or disagreeing with a statement. Results More than one-half (n = 23) completed the first round of the survey and 12 participated in the second. There was consensus on the need for a modifiable, fair, rational, and widely accessible multi-step approach to the assessment of older drivers. This would require the engagement and support of physicians and other health-care practitioners in identifying and reporting medically at-risk drivers of any age. At a societal level, alternatives to driving a personal motor vehicle should be developed. Conclusions An on-going dialogue about this complex issue is required. Decisions should be based on explicitly stated principles and informed by the best available evidence.